2017
DOI: 10.1155/2017/3491012
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Breast Hypertrophy: A Successful Breast Reduction of 14.9% Body Weight without Recurrence in a 5-Year Follow-Up

Abstract: Juvenile hypertrophy of the breast (JHB) is a rare and relentless disease affecting women in the peripubertal period. We present a 13-year-old girl with massive bilateral JHB, successfully treated with a breast reduction and free nipple graft technique. A total of 7300 grams of breast tissue had been removed, accounting for 14.9% of the patient's total body weight. Prophylactic hormonal therapy was not commenced. During the 5-year follow-up period, there was no recurrence and the patient remains satisfied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Traditional and faith healers have a lot of influence in our environment. In common with findings elsewhere our patients complained of intertrigo in the infra-mammary fold , (4) except that in our patients the intertrigo was smelly. Probably our warm environment enabled growth of bacteria that produce smelling gasses.…”
Section: Medical Researchsupporting
confidence: 92%
See 1 more Smart Citation
“…Traditional and faith healers have a lot of influence in our environment. In common with findings elsewhere our patients complained of intertrigo in the infra-mammary fold , (4) except that in our patients the intertrigo was smelly. Probably our warm environment enabled growth of bacteria that produce smelling gasses.…”
Section: Medical Researchsupporting
confidence: 92%
“…The weight of our study population ranged between 27 -33 kg , therefore we could not associate breast hypertrophy to an upsurge of obesity as noted in other studies . (2) We did not do breast imaging as it has been shown to be of little value due to dense breast tissue. (7) Although we did not detect malignancy in our histology specimens, the potential for malignancy in these hyperplastic breasts still exists.…”
Section: Medical Researchmentioning
confidence: 99%
“…This can lead to a significant limitation of the woman’s daily routine, resulting in psychological problems. Other entities, which must be differentiated from juvenile breast hypertrophy, are breast masses and idiopathic obesity [9, 10].…”
Section: Resultsmentioning
confidence: 99%
“…4 This is an extremely uncommon condition arising sporadically, though a familial case has been reported. 5 Hoppe et al 4 mentioned sixty five cases reported in the literature till 2010 A.D. Later on, Hisham et al 6 acknowledged nine more cases in addition to Hoppe et al from 2010 to 2016 A.D. Reduction mammoplasty with its modifications, is generally advisable to decrease the mass effect of the breast causing neck and back pain and to prevent hemorrhage and ulceration in the skin.…”
Section: Introductionmentioning
confidence: 99%